Composition and above Ground Biomass of Tree Species with Diameter Breast Height more than 5 cm at Gunung Stong State Park (GSSP) - Azhar, Siti Sarah (2018)
A study to determine composition and above ground biomass of tree species of Gunung Stong State Park, Kelantan was carried out in 0.16 ha plot. Four plots of 20 m x 20 m was established. Each plot then was divided into 4 subplots. A total of 392 individuals with diameter breast height (DBH) 5 cm and above were identiﬁed. Those trees comprise of 57 species in 31 families and 46 genera. The most diverse family was Anacardiaceae with ﬁve species followed by Anisophylleaceae and Apocynaceae. Dipterocarpaceae showed the highest basal area with a total of 57.39 ml/ha followed by Myrtaceae with an area of 10.19 ml/ha. The species that had the highest basal area was Shorea curtisii with an estimation area of 13.96 m’/ha. Total above ground biomass recorded in this study was 1801.58 t/ha. The highest total of above ground biomass was recorded by Dipterocarpaceae family with total 1129.92 t/ha. At species level, Shorea curtisii contributed 1075.22 t/ha from total biomass obtained. The Shannon-Weiner Diversity Index (H’) gave a value of 3.17 (H’ max I 4.04) with species richness and evenness value 9.38 and 0.78 respectively which considered as average for the species diversity of the area. Shorea curtisii from Dipterocarpaceae family was the most dominant species with the Important Value Index (IVi) of 129.40 %.